The Positive Impact of Having Served as a Danwei Leader on Post-retirement Life Satisfaction: Experiences in China - He, Li; Wang, Kun; Li, Tianyang; Wang, Jiangyin; Wang, Yuting; Zhang, Zixian; Wu, Yuanyang; Zhang, Shuo; Zhang, Siqing; Yang, Hualei (Frontiers in Psychology, 2021)
Relevance deprivation syndrome refers to feelings of incompetence among retired people caused by them leaving their high status or influential jobs. The question then arises: do people in positions of power, like Danwei leaders in China, have a lower life satisfaction post-retirement compared to other groups? This study investigated the influence of serving as a Danwei leader before retirement on retirees’ life satisfaction, as well as differences in this influence and the channels through which they are affected. Based on the data of 5873 respondents of the 2018 China Longitudinal Aging Social Survey, ordinary least-squares, ordered logistic regression, and propensity score matching models were used to investigate the influence, differences, and influential mechanisms of serving as a Danwei leader before retirement on retirees’ life satisfaction. We found that Danwei leaders experience a significantly positive impact on their life satisfaction post-retirement. Second, the positive impact of having served in this role on peoples’ post-retirement life satisfaction is related to the resulting higher income, social status, and better living habits. In contrast to the perspective of relevance deprivation syndrome, in China, having been a Danwei leader before retirement has a significantly positive impact on peoples’ life satisfaction post-retirement, with there being a significant difference observed among different types of retired Danwei leaders.